Microprocessor-based athlete health monitoring device based on heart rate and stride length calculation - Bakhteri, Rabia (Penerbit UTM Press, 2015)
Abnormal heart rate or low heart rate during exercise or recovery has been known to cause cardiac arrest and even sudden death in some cases. Similarly, research has shown that low step rate while running may be the causal factor for running injuries due to the force impact exerted and the extra loadings on the lower body joints. Commercial electronic devices used by athletes typically use either accelerometers or coil springs to estimate the step rate resulting in low accuracy. This paper describes the design a low-cost, wearable device that can help athletes monitor their physical activity while running or walking and report step rate, heart rate, distance covered, time elapsed and calories burnt with high accuracy. The system calculates the step rate by analyzing the signal generated from two Force Sensitive Resistors (FSRs) inserted above the insole of a running shoe which is connected to a microcontroller strapped to the athlete’s ankle. According to the experimental results, the prototype was found to have an average accuracy of 97% in measuring the distance covered.